Insulin Autoimmune Syndrome Treated with Plasmapharesis (Global Journal of Medical Research, 2020)
A 66-year male with a history of Central Serous Retinopathy presented with recurrent episodes of hypoglycemia. On evaluation, he was found to have insulin-mediated hypoglycemia with serum insulin of 300uIU/ml, C peptide 27.51ng/ml, when the blood glucose was 46mg/dl. High insulin levels above 100uIU/ml, led to suspicion of Autoimmune hypoglycemia and were confirmed by a high anti-insulin antibody titer of 300U/ml. Imaging was negative for Insulinoma. The patient was started on low dose oral prednisolone under ophthalmological monitoring, but as there was no symptomatic improvement, the dose was increased following which there was a flare-up of CSR. The patient was initiated on plasmapheresis following which his hypoglycemia improved with drop in anti-insulin antibody titers to 29U/ml. The patient was maintained on low dose steroids, which were tapered and stopped over the next six months with complete resolution of hypoglycemia and normalization of anti-insulin antibody titers.
Keywords: hypoglycemia; autoimmune; plasmapheresis; anti-insulin antibody